The Seno Otway pockmark field and its relationship to thermogenic gas occurrence at the western margin of the Magallanes Basin (Chile) - Kilian, R.; Breuer, S.; Behrmann, J. H.; Baeza, O.; Diaz-Michelena, M.; Mutschke Orellana, Erika E.; Arz, H.; Lamy, F. (My University, 2018)
Pockmarks are variably sized crater-like structures that occur in young continental margin sediments. They are formed by gas eruptions and/or long-term release of fluid or gas. So far no pockmarks were known from the Pacific coast of South America between 51 degrees S and 55 degrees S. This article documents an extensive and previously unknown pockmark field in the Seno Otway (Otway Sound, 52 degrees S) with multibeam bathymetry and parametric echosounding as well as sediment drill cores. Up to 31 pockmarks per square kilometer occur in water depths of 50 to > 100 m in late glacial and Holocene sediments. They are up to 150 m wide and 10 m deep. Below and near the pockmarks, echosounder profiles image acoustic blanking as well as gas chimneys often crosscutting the 20 to >30 m thick glacial sediments above the acoustic basement, in particular along fault zones. Upward-migrating gas is trapped within the sediment strata, forming dome-like features. Two 5 m long piston cores from inside and outside a typical pockmark give no evidence for gas storage within the uppermost sediments. The inside core recovered poorly sorted glacial sediment, indicating reworking and re-deposition after several explosive events. The outside core documents an undisturbed stratigraphic sequence since similar to 15 ka. Many buried paleo-pockmarks occur directly below a prominent seismic reflector marking the mega-outflow event of the Seno Otway at 14.3 ka, lowering the proglacial lake level by about 80 m. This decompression would have led to frequent eruptions of gas trapped in reservoirs below the glacial sediments. However, the sediment fill of pockmarks formed after this event suggests recurrent events throughout the Holocene until today. Most pockmarks occur above folded hydrocarbon-bearing Upper Cretaceous and Paleogene rocks near the western margin of the Magallanes Basin, constraining them as likely source rocks for thermogenic gas.
Keywords: None